Analysis of the Perioperative Course of Cardiac Surgery Patients with Coronary Artery Disease and Heart Valve Dysfunction - Olena K. Gogayeva (Ukrainian Journal of Cardiovascular Surgery, 2024)
The aim. To analyze the perioperative course of cardiac surgery patients with coronary artery disease (CAD) and heart valve dysfunction.Materials and methods. Retrospective analysis of 41 consecutive cardiac surgery patients (mean age 61.6 ± 7.8 years) with CAD and heart valve dysfunction who were operated on and discharged from the National Amosov Institute of Cardiovascular Surgery of the National Academy of Medical Sciences of Ukraine. All the patients underwent standard clinical and laboratory examinations, coronary angiography, on-pump cardiosurgical intervention.Results. The patients were divided into three subgroups: patients with post-infarction left ventricular aneurysm (LVA) combined with insufficiency of atrioventricular valves, n = 15 (36.6%); those with ischemic mitral insufficiency (MI), n = 11 (26.8%); and patients with CAD combined with aortic valve disease, n = 15 (36.6%). During echocardiographic study, decreased left ventricular ejection fraction was found in patients with LVA and with ischemic MI: 33 ± 6.4% and 39.4 ± 7.8%, respectively, and in patients with aortic valve disease, left ventricular ejection fraction averaged 48.2 ± 9.9% (p < 0.0001). According to the EuroSCORE II scale, the average risk was 11.8 ± 7.3%. All the patients were discussed by the heart team to choose the optimal method of cardiosurgical correction. In order to reduce the ischemic time, off-pump coronary bypass surgery was performed at the first stage, and the second stage was on-pump correction of valvular dysfunction. The average number of grafts was 2.8 ± 1.4, but the largest number of grafts was in the subgroup of ischemic MI: 4 ± 0.9 (p < 0.005). Mitral valve replacement in patients with LVA was performed through LVA in 12 patients. Acute heart failure, acute renal failure often developed in patients after correction of ischemic MI (p < 0.005). On the 1st day after the operation, there was an increase in average glucose values from 6.6 ± 2.8 to 10.3 ± 2.9 mmol/L (p < 0.0001), a decrease in glomerular filtration rate from 72.1 ± 15.3 to 57 ± 18.8 mL/min/1.73 m2 (p = 0.0001), the above indicators returned to the initial level at discharge (p < 0.0001).Conclusions. Off-pump myocardial revascularization in patients with CAD and dysfunction of the heart valves can significantly reduce the ischemic time. The method of mitral valve replacement through LVA developed in the department allowed to reduce the perfusion time (p = 0.0023) and the duration of the operation (p < 0.005). Preoperative discussion of examination data of patients by the heart team, thorough preparation for cardiac surgery, timely response to changes in laboratory parameters with correction of drug treatment avoid complications.